Meningkatkan Keterampilan Berpikir Tingkat Tinggi dan Sikap Ilmiah Melalui Eksperimen Berbasis Arduino - Dwi Fajar Saputri; Adi Pramuda; Soka Hadiati; Syarifah Fadillah; Eko Setyadi Kurniawan; Matsun (Postgraduate, University of Mataram, 2025)
In science learning, students' higher-order thinking skills (HOTS) and scientific attitudes are still low. Problems become increasingly complex when the COVID-19 pandemic minimally transforms students' interactions with their community environment. Innovation is needed to obtain an experimental model integrated with the Arduino Internet of Things to enhance HOTS and scientific attitudes. This research aims to obtain a valid and practical Arduino-based experiment model and its effect on HOTS and scientific attitudes. This research and development refers to Borg and Gall consisting of research and collecting of information, planning, initial product development, initial testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination. The research subjects involved were physics lecturers, education practitioners, and physics education students in West Kalimantan, Indonesia. Enhancing HOTS after implementing an experiment is calculated using the Multivariate Analysis of Variance. The arduino based experiments model has proven feasible, practical, and effectively applied to improve students' HOTS and scientific attitudes. The results become an innovative alternative laboratory work model to be used as a policy recommendation in higher education.